2021
DOI: 10.1055/s-0041-1735602
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Allograft Reconstruction of the Tibia Plateau for Posttraumatic Defects—A Novel Computer-Assisted Method Using 3D Preoperative Planning and Patient-Specific Instrumentation

Abstract: Background Surgical treatment of posttraumatic defects of the knee joint is challenging. Osteochondral allograft reconstruction (OCAR) is an accepted procedure to restore the joint congruity and for pain relief, particularly in the younger population. Preoperative three-dimensional (3D) planning and patient-specific instrumentation (PSI) are well accepted for the treatment of posttraumatic deformities for several pathologies. The aim of this case report was to provide a guideline and detailed description of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Through different studies on cadavers [90,91], this has shown an increase in accuracy and precision in both the harvest and placement of the graft [92]. In this field, Zaleski et al [93] applied CAS to plan an osteochondral allograft reconstruction for a post-traumatic tibial plateau defect, with precise pre-operative planning and the creation of patient-specific osteotomy guides (PSI). The operation was performed with lower operative times than conventional techniques and with higher precision of the allograft size and positioning.…”
Section: State Of the Art And Future Perspectivesmentioning
confidence: 99%
“…Through different studies on cadavers [90,91], this has shown an increase in accuracy and precision in both the harvest and placement of the graft [92]. In this field, Zaleski et al [93] applied CAS to plan an osteochondral allograft reconstruction for a post-traumatic tibial plateau defect, with precise pre-operative planning and the creation of patient-specific osteotomy guides (PSI). The operation was performed with lower operative times than conventional techniques and with higher precision of the allograft size and positioning.…”
Section: State Of the Art And Future Perspectivesmentioning
confidence: 99%